2021
DOI: 10.21203/rs.3.rs-278299/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical Simulation of Hardfacing Remanufacturing for Large-Scale Damaged Grinding Roller

Abstract: The present study is directed to the temperature and residual stresses fields in the hardfacing remanufacturing for a large-scale grinding roller with damage. For this purpose, a numerical procedure for the hardfacing process based on thermal cycle curve method was established, and the effectiveness of the proposed procedure was verified by the measurements of a multi-pass welding experiment with V-groove butt joint. Considering the characteristics of the hardfacing process, a local model of bead-on-plate weld… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In the study and analysis of the state of the problem, including the enterprises of Kazakhstan, Russia, Ukraine, Germany, India, Poland, and China, it was found that the following types are most widely used for recovering parts by hardfacing: manual arc surfacing, semi-automatic in shielding gases and automatic surfacing under a flux layer [10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study and analysis of the state of the problem, including the enterprises of Kazakhstan, Russia, Ukraine, Germany, India, Poland, and China, it was found that the following types are most widely used for recovering parts by hardfacing: manual arc surfacing, semi-automatic in shielding gases and automatic surfacing under a flux layer [10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%